IMPLEMENTASI KEBIJAKAN AMERICA FIRST ENERGY PLAN (AFEP) PADA MASA PEMERINTAHAN DONALD TRUMP (2017-2020): Isu Perubahan Iklim - Muhamad Kemal (2021)
This article discusses the implementation of the AFEP (America First Energy Plan) policy, this policy aims to achieve energy dominance in the United States. In the UN climate change convention, the United States is incorporated into an Annex 1 country, which means the United States has a historical responsibility in fighting climate change. The IPCC states that more than 50% of the greenhouse gases that cause climate change come from fossil fuels. In AFEP's policy to achieve energy dominance in the United States, the United States' fossil energy production, which had previously been held back during the Obama administration, was reopened during the Donald Trump administration. In short, the United States during the Obama administration became a country that paid attention to the issue of climate change, as evidenced by its actions in the international climate regime and a climate policy called the CAP (Climate Action Plan). However, during the Donald Trump administration, the United States became a rogue country in the international climate regime, as evidenced by its actions in the global climate regime and changing the CAP policy to AFEP. The research method used is a qualitative method with a descriptive analysis approach. The author uses a literature study technique, namely collecting data from books, articles, journals and the internet. The final result of this study shows that the implementation of the AFEP policy is contrary to international climate norms/regimes, but this policy is a bridge for the United States to achieve its national interests.